Histological Analysis of the Mandible in Patients with Type 2 Diabetes Mellitus for Implant-Prosthetic Rehabilitation. A Pilot Case-Control Study - Popa, Daniela; Iulia Juncar, Raluca; Juncar, Mihai (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
Diabetes mellitus has a major impact on the metabolic activity of a significant number of tissues. Its impact on the jaw bones cannot be neglected, especially if rehabilitation using prosthetic restorations supported on dental implants is intended. The aim of this study is to comparatively analyze vascularization, the degree of mineralization and the cellular component of the mandible in type 2 diabetes mellitus patients undergoing dental implant placement. For this study, eight patients assigned to two groups were selected. The study group included four patients with type 2 diabetes mellitus in whom dental implants were placed, and the control group comprised 4 patients without systemic pathology. The bone debris obtained after dental implant placement were collected and analyzed using hematoxylin-eosin and PAS–Alcian Blue staining. The results obtained indicated the presence of diabetic angiopathy in the mandible, a higher cellular density in the diabetic bone, and a lower degree of mineralization in the bone taken from patients of the study group. In conclusion, histological changes can be detected in the mandible of patients with type 2 diabetes mellitus compared to those without systemic disease, but their effect on bone healing cannot be quantified.